2019
DOI: 10.1007/s13280-018-1139-3
|View full text |Cite
|
Sign up to set email alerts
|

Social-ecological change in the Omo-Turkana basin: A synthesis of current developments

Abstract: This paper synthesizes current knowledge on the impacts of the Gibe III dam and associated large-scale commercial farming in the Omo-Turkana Basin, based on an expert elicitation coupled with a scoping review and the collective knowledge of an multidisciplinary network of researchers with active data-collection programs in the Basin. We use social-ecological systems and political ecology frameworks to assess the impacts of these interventions on hydrology and ecosystem services in the Basin, and cascading effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…The most recent developments are the Gilgel-Gibe III (hereafter 'Gibe III') dam, Africa's tallest, inaugurated in 2016, and the establishment of irrigated sugar estates, begun in 2013 and covering a projected 100,000 hectares (ha) as well as largescale cotton schemes [42], in addition to population growth and migration. There is considerable uncertainty about the impact of these social-ecological changes, as there has been relatively little study from the scientific community thus far [43][44][45][46][47]. However, prior work by [46] concluded that the Gibe III dam is posited to impact multiple ES and thus the livelihoods of the Lower Omo communities, mostly through loss of the seasonal flood.…”
Section: Mapping Ecosystem Servicesmentioning
confidence: 99%
See 4 more Smart Citations
“…The most recent developments are the Gilgel-Gibe III (hereafter 'Gibe III') dam, Africa's tallest, inaugurated in 2016, and the establishment of irrigated sugar estates, begun in 2013 and covering a projected 100,000 hectares (ha) as well as largescale cotton schemes [42], in addition to population growth and migration. There is considerable uncertainty about the impact of these social-ecological changes, as there has been relatively little study from the scientific community thus far [43][44][45][46][47]. However, prior work by [46] concluded that the Gibe III dam is posited to impact multiple ES and thus the livelihoods of the Lower Omo communities, mostly through loss of the seasonal flood.…”
Section: Mapping Ecosystem Servicesmentioning
confidence: 99%
“…There is considerable uncertainty about the impact of these social-ecological changes, as there has been relatively little study from the scientific community thus far [43][44][45][46][47]. However, prior work by [46] concluded that the Gibe III dam is posited to impact multiple ES and thus the livelihoods of the Lower Omo communities, mostly through loss of the seasonal flood. The affected ES can be summarized in three categories.…”
Section: Mapping Ecosystem Servicesmentioning
confidence: 99%
See 3 more Smart Citations